ELDER ABUSE SUBTYPES REPORTED TO THE NATIONAL CENTER ON ELDER ABUSE. (11th November 2018) - Goodman, M; Weissberger, G; Nguyen, C; Mosqueda, L; Schoen, J; Han, D
Abstract: This study examined the frequency of six types of elder abuse and types of abuser-victim relationships identified from calls to the National Center on Elder Abuse call center (NCEA-CC) between 08/2014-06/2017. The NCEA-CC receives calls from individuals seeking assistance in reporting incidents or requesting general information on elder abuse. Calls were classified into six subtypes (financial, physical, sexual, emotional, neglect, and self-neglect) using the Center for Disease Control's uniform definitions for elder abuse. Frequencies of elder abuse subtype and abuser-victim relationship data were coded. We identified 775 calls (664 specified abuse subtype; 616 specified relationship) alleging elder abuse. Abuse subtype was coded in the following frequencies: financial (63.3%), emotional (27%), neglect (23.6%), physical (10.4%), sexual (1.4%), and self-neglect (1.1%). Abuse by a family member was most frequently alleged (49%), followed by abuse by a medical caretaker (20.1%), a non-caretaker acquaintance (16.7%), a stranger (7.8%), a non-medical caretaker (5.2%), and self-neglect (1.1%). The most commonly alleged abuse type by a family member was financial (67%). Results indicate that financial abuse is the most commonly alleged form of elder abuse to the NCEA-CC, and suggest a family member might be likely to commit this type of abuse. This supports findings from a large survey study that found financial mistreatment by family to be the most prevalent form of abuse, but is contrary to another study that found emotional abuse by family to be most prevalent. Different methodological approaches could account for divergent findings across studies.